Aminopenicillin‐associated exanthem: lymphocyte transformation testing revisited. Issue 12 (December 2014) - Trautmann, A.; Seitz, C. S.; Stoevesandt, J.; Kerstan, A.
Summary Background The lymphocyte transformation test (LTT) has been promoted as in‐vitro test for diagnosis of drug hypersensitivity. For determination of statistical LTT sensitivity, series of patients with clinically uniform reactions followed by complete drug hypersensitivity work‐up are mandatory. Assessment of LTT specificity requires control patients who tolerated exposure to the drug studied. Objective To prospectively determine the diagnostic value of the LTT in a clinically and diagnostically well‐defined series of patients. Methods Patients with exanthematous skin eruptions after ampicillin (AMP) intake were included in this study. After exclusion or confirmation of delayed‐onset allergic AMP hypersensitivity by skin and provocation testing, two independent LTTs were performed: one standard LTT and a modified LTT with additional anti‐CD3/anti‐CD28 monoclonal antibody stimulation. Results By testing, delayed‐onset allergic AMP hypersensitivity was diagnosed in 11 patients and definitely ruled out in 26. The standard LTT reached a diagnostic sensitivity of 54.5% while the modified LTT yielded 72.7%. However, the methodical test modification resulted in a decline of specificity from 92.3% (standard LTT) to 76.9%. Conclusions and Clinical Relevance In cases of AMP‐associated exanthems, the diagnostic value of the LTT compared with routine allergy testing is limited. When evaluating such exanthems, provocation testing remains the gold standard. Delayed reading of intradermal skin tests remains most useful to avoid positive provocation reactions.